Mapping our Territories. - Kiendl, Anthony; Martin, Lee-Ann; Walter Phillips Gallery, The Banff Centre, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts, 2002)
Artists Delia Cross Child, Faye HeavyShield, Frederick McDonald and Lionel Peyachew introduce us to their home territories. Although born and living within Treaty areas 6, 7 and 8, they articulate contemporary Aboriginal perspectives within a distinctly Post-Treaty context that underscores deep personal and cultural connections. The exhibition becomes a collective map connecting history and community with place.
Engels
Mapping our Territories, Walter Phillips Gallery - The Banff Centre for the Arts Banff, August 2- October 6, 2002
boek
Keywords: Cross Child, Delia; HeavyShield, Faye; McDonald, Frederick; Peyachew, Lionel